Vocalizations of male bearded seals, Erignathus barbatus: classification and geographical variation (Norwegian Polar Institute, 2008)
Comparative studies of vocal repertoires over the geographical range of a species can improve ourunderstanding of the function and evolution of animal vocalizations. They may also help to elucidaterelationships between populations, where genetic studies are missing or difficult to perform. We recordedmale bearded seal vocalizations from four sites throughout their Arctic distribution. We measured 16parameters for each vocalization and examined variability using classification tree analyses. There werefour major call categories: trill, ascent, sweep and moan. Trills divided further into three subcategories:trills with ascent/plume, long trills and short trills. Not all call categories were present at all sites: the ascentoccurred only in Alaska and western Canada, the sweep occurred only in Svalbard and in the High CanadianArctic, and the trill with ascent/plume occurred at all sites except Svalbard. Geographical differencesbetween sites were apparent in repertoire size as well as in vocal structure. Furthermore, an eastwestgradient in structural similarities between call types was apparent. The vocal repertoire of bearded sealsseemed to be relatively stable; for example, over a period of 16 years no calls were lost or added to theAlaskan repertoire. The most likely explanation for the observed vocal differences between sites is thegeographical isolation of populations by physical distance. Other factors, such as varying ecological influences(e.g. adaptation to varying ice habitats) or sexual selection, may also contribute to vocal variabilityand result in the observed geographical variation.